Pricing and Cooperation in advertisment in a two levels supply chain using game thory - Ata Allah Taleizadeh; Zahedeh Cheraghi (مجله مدل سازی در مهندسی, 2015)
Cooperation in advertising is a marketing strategy in which retailer performs local advertisements and manufacturer pays a fraction of total cost. In this paper cooperation in advertising and pricing decisions in a two-layer supply chain including single manufacturer and single retailer is investigated. In order to study the optimal decisions of chain members under different assumptions, four models based on the game theory approaches, are developed. Three non-cooperative games including, Nash, retailer-leader, manufacturer-leader and one cooperative game, are those cases under which models are developed. The convexity of the objective function of each case is proved and at the end for each case numerical example is presented and sensitivity analysis is performed.